2005
DOI: 10.1007/s00280-005-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus celecoxib (GECO) in advanced pancreatic cancer: a phase II trial

Abstract: GEM in combination with celecoxib showed low toxicity, good clinical benefit rate and good disease control. Further clinical investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…It has a multifunctional role in pancreatic cancer development, being implicated in angiogenesis (for example through upregulation of VEGF), proliferation, invasiveness and immunosuppression. Preclinical studies of COX-2 inhibitors are encouraging 157 -159 , and phase II studies using the selective COX-2 inhibitor celecoxib have yielded promising data 160,161 , although further studies are warranted. Two studies found COX-2 expression to be a prognostic factor independent of conventional clinicopathological parameters 43,44 , but its prognostic significance remains to be confirmed 39,125,153,162 -165 .…”
Section: Cyclo-oxygenasementioning
confidence: 98%
“…It has a multifunctional role in pancreatic cancer development, being implicated in angiogenesis (for example through upregulation of VEGF), proliferation, invasiveness and immunosuppression. Preclinical studies of COX-2 inhibitors are encouraging 157 -159 , and phase II studies using the selective COX-2 inhibitor celecoxib have yielded promising data 160,161 , although further studies are warranted. Two studies found COX-2 expression to be a prognostic factor independent of conventional clinicopathological parameters 43,44 , but its prognostic significance remains to be confirmed 39,125,153,162 -165 .…”
Section: Cyclo-oxygenasementioning
confidence: 98%
“…Recently, anti-COX-2 agents have been documented to have antitumor activity, and some are now being tested as therapies for various cancers [26-29, 31, 35-37] . The antitumor effect of anti-COX-2 agents has also been confirmed in experimental research on pancreatic cancer cells [38][39][40][41] , and clinical investigations have already started [42][43][44] .…”
Section: Discussionmentioning
confidence: 74%
“…We now know that COX-2 inhibition impacts negatively on cardiac and renal, which causes to serious side effects of prolonged inhibition of this pathway (34). In pancreatic cancer clinical trials, celecoxib in combination with standard chemotherapeutic drugs was found to be modestly effective in some studies but in other studies the effectiveness was limited by toxicity (35)(36)(37)(38)(39). From all of the available data it appears that inhibition of COX-2/PGE2 pathway is effective, but celecoxib does not appear to be the best therapeutic to inhibit this pathway.…”
Section: Discussionmentioning
confidence: 98%